TINJAUAN HUKUM TENTANG PENGURUSAN HARTA KEKAYAAN ANAK DI BAWAH UMUR YANG BERASAL DARI PEWARISAN OLEH WALI AYAH/IBU (TINJAUAN HUKUM PERDATA BW) - M. Syakdan Hamidi Nst (University of North Sumatera, 2013)
Abstrak : In general, the element of age play a role in determining whether or not a person competent to act in legal actions. According to the inheritance, heirs entitled to inheritance may also include children who are under age. Minors are usually represented by parents who lived the longest include arrangements for the property to be received. It contains an obligation to take care of the burden of responsibility both on the property and the items on the results of these items, and the responsibility it carries an obligation also provide calculations and accountability in carrying out these responsibilities the guardian shall take care of children under supervision and such assets as well as possible. The main issues to be answered in this study is How the implementation of the end of the rule guardian to a minor under civil law BW?, How can the rights and obligations of trustees in the management of assets of a minor by a parent as guardian derived from inheritance, How is the maintenance of property wealth minors obtained from BW civil inheritance law. This research was conducted with normative juridical approach, the approach that focuses on the legal aspects of analyzing the problem from the point of view / by law or the laws that apply in this use case studies Civil Code and the Religious Court Decision No. 054 / Pdt.P/2010/PA JP. The results of this study showed that parental authority is valid since the child was born into this world until the child reaches the age of majority under applicable law, as long as both parents were engaged in a marital relationship, not only for the children themselves but also against objects or wealth of the child. Based on the discussion above, the writer can conclude that the control of parents or guardians of children under the age of not only the child but also to property or wealth of the child and the whole must be on guard as well as possible for the sake of the child's life. So that parents / guardians are fully responsible for the survival of the child until she was an adult. Advice can be given in this study is that trustees should carry out their responsibilities in the best possible, and the child's assets should be recorded and maintained as well as possible with regard to the provisions that are required by law. Keywords: Management of Intellectual property, inheritance